Atmospheric pollution history at Linfen (China) uncovered by magnetic and chemical parameters of sediments from a water reservoir. (September 2015) - Ma, Mingming; Hu, Shouyun; Cao, Liwan; Appel, Erwin; Wang, Longsheng
Abstract: We studied magnetic and chemical parameters of sediments from sediments of a water reservoir at Linfen (China) in order to quantitatively reconstruct the atmospheric pollution history in this region. The results show that the main magnetic phases are magnetite and maghemite originating from the surrounding catchment and from anthropogenic activities, and there is a significant positive relationship between magnetic concentration parameters and heavy metals concentrations, indicating that magnetic proxies can be used to monitor the anthropogenic pollution. In order to uncover the atmospheric pollution history, we combined the known events of environmental improvement with variations of magnetic susceptibility (χ) and heavy metals along the cores to obtain a detailed chronological framework. In addition, air comprehensive pollution index (ACPI) was reconstructed from regression equation among magnetic and chemical parameters as well as atmospheric monitoring data. Based on these results, the atmospheric pollution history was successfully reconstructed. Highlights: Magnetic proxies can be used to monitor the heavy mental pollution in sediments. Accurate age model was obtained using known events of environmental improvement. Regression equation was obtained among sediment records and monitoring data. Atmospheric pollution history was quantitatively reconstructed. Abstract : Atmospheric pollution history was quantitatively reconstructed using magnetic and chemical records of reservoir sediments combined with atmospheric monitoring data.